Coaching psicopedagógico para la promoción del desarrollo personal en estudiantes de séptimo año de egb en la escuela 18 de octubre - Jurado Puente, Jovanna Margarita (2025)
The present research work entitled “Psychopedagogical coaching for the promotion of personal development in seventh grade students of EGB at Escuela 18 de octubre” addresses the importance of psychopedagogical coaching as a strategy to strengthen the personal development of students, focusing on key areas such as self-esteem, social skills, motivation and emotional management. The research is based on theories of learning and human development, highlighting the influence of Lev Vygotsky and Carl Rogers in the creation of favorable educational environments. A qualitative approach within the interpretative paradigm is employed, using techniques such as surveys, the students' experience with psycho-pedagogical coaching. The results obtained show that this methodology contributes significantly to improve self-confidence, self-regulation capacity and conflict resolution among students. Areas of improvement were identified in the management of stress and anxiety, which highlights the need to reinforce emotional regulation strategies in the classroom. The research also emphasizes the importance of training teachers in psycho- pedagogical coaching techniques and recommends its structural integration into the school curriculum to ensure a lasting impact on the integral formation of students. As a conclusion, it is highlighted that psycho-pedagogical coaching not only favors the individual wellbeing of students, but also improves classroom dynamics, promoting a more collaborative and motivating environment. To guarantee the sustainability of these results, the implementation of continuous accompaniment programs, progress monitoring and feedback between teachers, students and families is suggested, thus ensuring a more inclusive education focused on the personal development of students.